Collaborative practices and partnerships across school mental health and pediatric primary care settings. Issue 3 (1st October 2016) - Arora, Prerna G.; Bohnenkamp, Jill H.
Abstract: Education and primary care sectors have been called upon to attend to shortages in access to mental health services among children and adolescents. In response, these settings have increasingly attempted to address this need, though research exploring such collaborative efforts remains limited. The current special issue features research examining collaborations between school and paediatric primary care settings, bringing original research and clinical examples to bear on partnerships which leverage opportunities to improve access to high-quality mental health care. Articles in this special issue underscore the positive youth outcomes associated with effective collaboration across these systems and augment the literature describing innovative and successful approaches to this work. Further, articles in this issue identify barriers to collaborative efforts and present opportunities for future research and practice.